A Witch in Winter - Warburton, Ruth (Great Britain, Hodder Children's, 2012)
Anna Winterson doesn't know she's a witch and would probably mock you for believing in magic, but after moving to the small town of Winter with her father, she learns more than she ever wanted to about power
Keywords: English-Fiction